Exploring agency and justice in Devadasis through the lens of Dharma in the Undoing Dance and Desire of the Moth - Kumar, Yusintha Othaya; Mani, Manimangai (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article delves into the themes of agency and justice as portrayed in the novels The Undoing Dance by Srividya Natarajan and Desire of the Moth by Champa Bilwakesh, focusing on the experiences of Devadasis, or temple dancers, in colonial and post-colonial South India. Utilising the concept of dharma from Hindu philosophy, this paper examines how the protagonists rise above their marginalised status and assert agency in pursuit of justice through their participation in classical dance. Through this bond, they discover purpose and liberation in their ability to express themselves, as classical dance transcends social hierarchy, discrimination, and injustice. While justice has been a prominent theme in Western literature, there remains a noticeable gap in Indian literature. This exploration thus creates a paradigm shift by shedding light on the empowering aspect vividly expressed through their participation in the classical dance form called Bharatanatyam, which allowed them to rise above their injustices rather than confining them within the societal framework of South India. This nuanced perspective forms the crux of this study, suggesting a more transformative view that highlights the ethical aspects of their battle, creating a sense of agency and justice through their dharma. © 2024 Penerbit Universiti Kebangsaan Malaysia.